GAGASAN PENDIDIKAN PROFETIK: SEBUAH ALTERNATIF PENDIDIKAN MASA KINI - Doni Ahmad Saefuddin; Sugiyono Sugiyono; Khaerul Wahidin (Jurnal An-Nufus, 2021)
This article discusses the purpose of education, namely developing the potential of students to become human beings who believe and fear Allah SWT so that they have a noble personality plus self-competence in accordance with a prophetic vision that refers to the Prophet Muhammad as a role model. In writing this article, the researcher uses the methodology of studying Islamic literature by referring to the subject matter of professional education. In achieving these educational goals, there are three main frameworks (if referring to QS. Ali Imran: 110): First, humanization (amar ma'ruf) or humanizing humans, where students are used as subjects of education, not objects of education; Second, liberation (directed nahi mungkar) or having a place for students to face critical problems that occur in the midst of society so that they are able to find solutions; Third, transcendence (tu'minuuna billah), which is the process of making students recognize the virtues and have the dimension of moral cultivation